Strength training with blood flow restriction in HIV patients positive: a case study - Siqueira Paiva de Souza, Thiago (2021)
This study purposed to compare responses of segmented neutrophils, monocytes, lymphocytes, and T lymphocyte Clusters of Differentiation 4 and 8 (CD4+ T and CD8+ T) to blood flow restriction training in HIV patients. Two HIV patients participated in the study, one patient had a sedentary lifestyle, and the other was physically active. HIV-infected female patients performed a blood flow restriction training session consisting of two exercises: flat bench press and knee extension. Blood (6 mL) was collected for analysis prior to training, immediately after training, and 30 minutes after. After blood flow restriction training, percentage changes in the number of leukocytes were observed in both patients. Monocytes showed different responses in the two patients: a decrease in monocyte count was seen in the physically active, and an increase was observed in the sedentary lifestyle. Lymphocytes showed a higher increase in the physically active than in the sedentary lifestyle. There was an increase in the CD4+ / CD8+ T lymphocyte ratio in both patients. It was concluded blood flow restriction promoted acute inflammation after training, shown by changes in immune cell counts. These changes did not promote immunosuppression; instead, an increase in CD4+/CD8+ T lymphocyte ratio was observed; and HIV-infected came similar results. Keywords: muscle strength; acquired immune deficiency syndrome; HIV-1; exercise; Kinanthropometry